A Patient With Parenteral Nutrition–Dependent Short Bowel Syndrome and Cardiovascular Disease With 4‐Year Exposure to Teduglutide. (7th January 2015) - Compher, Charlene; Levinson, Katherine Boothe; Cambor, Carolyn L.; Stoner, Nancy; Boullata, Joseph I.; Piarulli, Amanda; Kinosian, Bruce
Abstract : Clinical trials of the glucagon‐like peptide 2 analogue teduglutide resulted in approval of the drug by the Food and Drug Administration in 2012 as a treatment for parenteral nutrition–dependent short bowel syndrome in adults. This report presents the case study of a man with short bowel syndrome caused by portal vein thrombosis who had 4 years exposure to the drug at the time of his death due to cardiovascular disease.